DAMPAK PERTAMBANGAN ILEGAL TERHADAP KUALITAS AIR DAN KESEHATAN MASYARAKAT DI KABUPATEN POHUWATO - Patila, Jein; anu, Zulkarnain; Setiyowati, Endah (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
Illegal mining is a growing problem in Indonesia, especially in Pohuwato Regency, Gorontalo, which is known for its abundant mineral resources. Illegal mining activities not only involve illegal exploitation of natural resources, but also have a significant impact on water quality, public health, and ecosystems around mining areas. This research aims to explore The effects of illegal mining on water quality and public health are significant and concerning. Pohuwato Regency. The research method used is a qualitative approach with data collection through in-depth interviews, direct observation, and documentation studies related to social and environmental impacts. The results showed that water pollution caused by the use of hazardous chemicals, such as mercury and cyanide, has led to changes in water conditions that are polluted and unfit for consumption. The impact on public health includes various diseases, such as skin diseases, digestive disorders, and heavy metal poisoning that harms the nervous system. In addition, environmental degradation caused by deforestation, soil erosion and declining water flows have worsened the quality of life for communities, who are increasingly pressed for clean water. The decline in water quality also has a direct impact on the agriculture and fisheries sectors, which are the main livelihoods of the local population. This damage not only threatens food security, but also adds to the economic burden on already vulnerable communities.